Seroprevalence of Ehrlichia canis and of Canine Granulocytic Ehrlichia Infection in Dogs in Switzerland - Pusterla, Nicola (American Society for Microbiology, 1998)
Serum samples from 996 dogs in Switzerland were examined for antibodies to Ehrlichia canis and to the agent causing canine granulocytic ehrlichiosis (CGE). Ehrlichiosis, borreliosis, and systemic illness not associated with ticks were suspected in 75, 122, and 157 of these dogs, respectively. The remainder of the serum samples were obtained from clinically healthy dogs which resided north (n = 235) or south (n = 407) of the Alps. The serum samples were tested by an indirect immunofluorescence technique for antibodies to the two agents incriminated, E. canis and Ehrlichia phagocytophila, a surrogate marker of the agent of CGE. Twenty-two of 996 (2.2%) serum samples had antibodies to E. canis and were distributed as follows: 20 of 75 (26.7%) samples from dogs suspected of having ehrlichiosis, 1 of 122 (0.8%) from dogs suspected of having borreliosis, and 1 of 407 (0.2%) from healthy dogs which resided south of the Alps. Of the 75 (7.5%) serum samples that had antibodies to E. phagocytophila, significantly more samples were from ill dogs than from healthy dogs. Among the sera from healthy dogs, antibodies to E. phagocytophila were significantly more prevalent in the north. Because seropositive dogs had a history of travel outside Switzerland and because Rhipicephalus sanguineus is found exclusively south of the Alps, it was presumed that, in contrast to the agent of CGE, E. canis is not indigenous to Switzerland.